2008
DOI: 10.1152/japplphysiol.00951.2007
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cardiovascular effects of neonatal dexamethasone treatment: hemodynamic follow-up by left ventricular pressure-volume loops in rats

Abstract: Bal MP, de Vries WB, van Oosterhout MF, Baan J, van der Wall EE, van Bel F, Steendijk P. Long-term cardiovascular effects of neonatal dexamethasone treatment: hemodynamic follow-up by left ventricular pressure-volume loops in rats. J Appl Physiol 104: 446-450, 2008. First published December 13, 2007 doi:10.1152/japplphysiol.00951.2007.-Dexamethasone is clinically applied in preterm infants to treat or prevent chronic lung disease. However, concern has emerged about adverse side effects. The cardiovascular sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…In the young Dex-treated rats, Vw was reduced despite this cellular hypertrophy later in life, but in the 50-wk-old animals in which also myocyte width was increased substantially, these hypertrophic processes are likely to be compensatory. Despite these compensatory mechanisms, we recently reported on the loss of systolic cardiac function in this group of 50-wk-old Dex-treated rats (15), which may indicate that cardiomyocyte hypertrophy did not fully compensate for the lower number of cardiomyocytes. Furthermore, histologic analysis of the 50-wk-old Dex-treated hearts revealed more foci of inflammation associated with myocytolysis, which may indicate "wear-out" of the remaining cardiomyocytes.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In the young Dex-treated rats, Vw was reduced despite this cellular hypertrophy later in life, but in the 50-wk-old animals in which also myocyte width was increased substantially, these hypertrophic processes are likely to be compensatory. Despite these compensatory mechanisms, we recently reported on the loss of systolic cardiac function in this group of 50-wk-old Dex-treated rats (15), which may indicate that cardiomyocyte hypertrophy did not fully compensate for the lower number of cardiomyocytes. Furthermore, histologic analysis of the 50-wk-old Dex-treated hearts revealed more foci of inflammation associated with myocytolysis, which may indicate "wear-out" of the remaining cardiomyocytes.…”
Section: Discussionmentioning
confidence: 67%
“…The rats were weaned on d 21 and studied at 4, 8, or 50 wk of age. Before being killed for the current histopathological study, hemodynamic measurements were performed that were reported elsewhere (14,15). All groups at the various ages (4-, 8-, and 50-wk-old) consisted of eight rats.…”
Section: Animals the Study Protocol Was Approved By The Animal Researchmentioning
confidence: 99%
“…Yet synthetic glucocorticoid exposure may be harmful to other tissues and organs (Ortiz et al, 2003;Shoener et al, 2006;Kamphuis et al, 2007;Bal et al, 2008;Davis et al, 2011;Kelly et al, 2012). Recently, we demonstrated that treatment of newborn rats with dexamethasone during a critical window of the heart development inhibited cardiomyocyte proliferation, stimulated premature cardiomyocyte binucleation, and reduced the total cardiomyocyte number in the heart .…”
Section: Introductionmentioning
confidence: 98%
“…Excessive 'catch-up' growth may be compounded when hypertension development associated with exposure to elevated systemic glucocorticoid levels contributes to cardiac loading. Recent studies by Bal et al [45,46] suggest that neonatal dexamethasone treatment is associated with cellular hypertrophy, increased collagen deposition and systolic dysfunction in the adult rat heart at 50 weeks of age. Interestingly, following neonatal dexamethasone exposure, the ventricular weight to body weight ratio was reduced at 4 weeks of age, but was not different at 50 weeks of age, indicative of partial cardiac 'catch-up' growth.…”
Section: Discussionmentioning
confidence: 99%